Research on application of network slice technology in mine communication network - LIU Haipeng; ZHOU Shuqiu (Gong-kuang zidonghua, 2020)
Aiming at problems of low resource sharing efficiency, difficult maintenance and upgrade, and inflexible and inefficient vertical service deployment and configuration caused by multi-source heterogeneous structure of mine communication network, network slice(NS) technology was applied to mine communication network. Mine communication network architecture based on NS was constructed. Deployment of NS in mine communication network is divided into service instance layer, network slice instance(NSI) layer and resource layer, which respectively correspond to application layer, transmission layer and perception layer in mine communication network. The service instance layer is responsible for underground service creation and life cycle maintenance. By abstracting device into independent NS, the NSI layer generates customizable, logically independent and service isolated NSI for customized use by service subscribers with different requirements. The resource layer is responsible for providing computing, storage, forwarding, wireless access and other functions to the NSI layer. By dynamically modifying key performance indicators parameters of each network in NS template, management of NSI life cycle is realized, which meets service requirements of customization and flexible use of NS. Through dynamic configuration and management of NSI isolation attributes and global operation of NSI isolation requirements, NS isolation is realized to achieve purpose of non-interference among services carried by NS. NS was divided according to latency sensitive, bandwidth sensitive and connection quantity sensitive underground services, and NS working state under typical underground services was given, which could meet flexible configuration requirements of mine communication network for differentiated vertical services.